Ten Influential Point-of-Care Ultrasound Papers: 2021 in Review. (November 2022) - Millington, Scott J.; Arntfield, Robert T.; Koenig, Seth J.; Mayo, Paul H.; Vieillard-Baron, Antoine
The ongoing rapid expansion of point-of-care ultrasound (POCUS) and its corresponding supporting literature leaves the frontline clinician in a difficult position when trying to keep abreast of the latest developments. Our group of POCUS experts has selected ten influential POCUS-related papers from the past twelve months and provided a short summary of each. Our aim is to give to emergency physicians, intensivists, and other acute care providers key information, helping them to keep up to date on rapidly evolving POCUS literature.